Next slide please: the politics of visualization during COVID-19 press briefings - Allen, WL; Bandola-Gill, J; Grek, S (Taylor & Francis, 2023)
How do governments visually communicate policies, and what does this reveal about actors’ political objectives? Governments strategically narrate their priorities, yet few studies examine this process through visual modes. We contribute to theoretical and empirical understanding in policy studies by focusing on the UK government’s COVID-19 response through its daily press briefings during the first wave of 2020. Combining quantitative changepoint and content analysis with qualitative discourse analysis, we examine all 79 sets of slides when briefings occurred. We identify a reactive phase focused on communicating knowledge about the pandemic in a boundedly rational manner, and a proactive phase that created new policy-based narratives of the pandemic. Besides contributing to emerging pandemic-related policy scholarship, we argue that conceiving these visualizations as visual narrative assemblages is relevant more broadly because it shifts attention to the interaction and interdependence of multiple visualizations as they enable policymakers to perform their authority to govern.